PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI MOBIL MEREK HONDA JAZZ PADA PT. ARISTA AUTO PRIMA CABANG PEKANBARU - Nurul Huda; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Effect of Integrated Marketing Communication On Consumer Decision Buyer for Brand Car of Honda Jazz In Showroom Arista Auto Prima Pekanbaru. The method that was used in this study is a survey explanatory. To collect the data, the authors used questionnaires and documentation. To determine the effect of Integrated Marketing Communication on Consumer Decision Buyer for brand car of Honda Jazz in showroom Arista Auto Prima Pekanbaru , the authors used a multiple linear regression analysis. Variable X in this study is the integrated marketing communication, while variable Y is. The number of samples in this study was 82 respondents, sample collection technique is random sampling technique. Processing test questionnaires were performed using the Statistics Product and Service Solution (SPSS) version 19.0. Result of this study demonstrate the effect of influence of Integrated Marketing Communication on Consumer Decision Buyer for brand car of Honda Jazz in showroom Arista Auto Prima Pekanbaru is 19.9%. There fore H0 is rejected and Ha is accepted because there is influence of Integrated Marketing Communication on Consumer Decision Buyer for brand car of Honda Jazz in showroom Arista Auto Prima Pekanbaru